Nietzsche's aesthetic turn : reading Nietzsche after Heidegger, Deleuze, and Derrida - Winchester, James J. (Albany : State University of New York Press, 1994)
"This clearly written book, intended for both specialists and nonspecialists, focuses on Nietzsche's later writings, where he appears unsystematic and indifferent to questions of truth. "This book undertakes three important and related tasks. The first is a comprehensive analysis of Nietzsche's notoriously slippery writings; the second is a critique of several major positions in Nietzsche interpretation; and the third is a proposal for a kind of philosophizing 'beyond the truth standard, ' a philosophy without nostalgia for the lost grounds of truth. These topics are important today, and form the basis for a considerable debate about the significance of Nietzsche in particular and his role in shaping the twentieth century in general."--Book cover
Introduction -- 1. The Eternal Return and the Plurality of Nietzsche's Voices -- 2. A System of Will to Power? -- 3. Deleuze's Reading of Nietzsche As a Pluralist -- 4. Philosophical Constructions in the Age of the Loss of Absolutes -- 5. Necessary Fictions -- 6. Nietzsche's Aesthetic Criteria -- 7. Aesthetics and Morality: The Moral Implications of the Aesthetic Turn.
Includes bibliographical references (pages 167-202) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Aesthetics; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Esthétique.; Nietzsche, Friedrich Wilhelm, -- 1844-1900; PHILOSOPHY -- History & Surveys -- Modern; Aesthetics